USING AUTHENTIC MATERIAL IN INCREASING STUDENT READING ABILITY - Emeliya Sukma Damanik (UIN Sumatera Utara, 2017)
This study talks about the use of authentic material to increase student ability in reading. The research method uses classroom action research. It conducted to the students of IAIN sultan Maulana Hasanuddin Banten. Based on the data, the research resulted that the use of authentic material can increase student reading ability. It can be seen from the range of percentage from the first cycle and second cycle. The students also hold positive attitude toward the use of authentic material in reading class. The data shows that the student tends to choose agree and strongly agree. But, the use of authentic material is also needs appropriate technique, method and strategy to support them. Key word: authentic material, reading